Free trade agreements and regional alliances: support from Latin American legislators - Asbel Bohigues; José Manuel Rivas (Revista Brasileira de Política Internacional, 2019)
Abstract The creation of international organizations and the signature of free trade agreements have become common in Latin America. However, few studies have tackled the attitudes of political elites. This work aims to analyze the determinants of support by Latin American legislators for free trade agreements with the US and the EU, and for the Pacific Alliance and ALBA. Results show that ideology, pro-state/market positions, and trustworthiness vis-à-vis Chinese and Russian governments are the main predictors.